TRANSFORMATION OF LEMONGRASS PLANTS INTO ENVIRONMENTALLY FRIENDLY MOSQUITO REPELLENT SPRAYS: EMPOWERMENT AND DIGITAL BRANDING IN WRINGINANOM VILLAGE, MALANG REGENCY - Priyono, Achmad Agus; Saraswati, Ety; Dimas, Moh Fahrezi; Taufiqulhakum, M Fadhila; Isma, Viona Aulia; Amalyani, Meifiana (JURNAL EDUCATION AND DEVELOPMENT, 2025)
The Thematic Service Undergraduate Candidate Program (KSM-T) of the Islamic University of Malang in Wringinanom Village aims to overcome public health problems and empower the local economy through the use of lemongrass plants as raw materials for natural mosquito repellent sprays and optimize product branding through social media. These activities include socialization, production training, and digital marketing. The results showed increased people's understanding and skills in processing lemongrass into effective, safe, and environmentally friendly products. Branding optimization through social media has succeeded in increasing brand awareness and sales, positively impacting health, the economy, and the environment. This program shows the importance of collaboration between local potential and digital technology as a sustainable approach to community empowerment.